The Impact of New Municipalities Policies and Regulations On the Hospitality Sector in the Kingdom of Saudi Arabia - Jifri, Ali; Dwyihi, Abdulallah (The Arab Journal of Administration, 2023)
The aim is to study new policies and legislation in the field of hospitality and see their impact on improving the tourism environment. The study will be based on institutional theory from the perspective of (Scott, 2004). The study of the dynamics of the impact of regulations and legislation to the world as a cramping (Kitching, 2018) direct and indirect impact. Using the mixed qualitative and quantitative method. We started with the qualitative approach to find out the directions of legislators and the objectives of legislation designed for the hotel and restaurant sectors through personal interviews of stakeholders and legislators and then coding the responses. To analyze the data, we will use Nvivo. The results helped us build the questionnaires that we sent to the beneficiaries to know the reality of the quality of these legislations and their impact on improving the environment of the hotel and restaurant sector, and the questionnaires will be analyzed statistically using the SPSS program. The study found that the negative effects of the low quality of legislation on the private sector. An indirect effect is the lack of trust between the private sector and municipal legislators due to poor communication in the legislative making process and their lack of participation.